الضوابط القانونية لإطلاق الأقمار الصناعية في الفضاء الخارجي طبقاً لاتفاقيات الفضاء - شنوف, بدر (جامعة الوادي University of Eloued, 2018)
يهدف هذا البحث إلى بيان الإطار القانوني لعمل الأقمار الصناعية في الفضاء الخارجي، وما هي أهم الاتفاقيات الدولية التي نظمت عملها، موضحاً تعريف القمر الصناعي وأهم أنواعه وكذا سلطة الإطلاق، معرجاً على أهم المبادئ التي تحكم أنشطة الدول في إطلاقها للأقمار الصناعية، التي نستطيع من خلالها بيان أحكام المسؤولية الدولية عن الأضرار التي تسببها الأقمار الصناعية، للوصول إلى تحمل دولة الإطلاق للمسؤولية الدولية، التي قد تكون مسؤولية مطلقة أو مسؤولية مستندة على الخطأ. The aim of this research is to clarify the legal framework for the operation of satellites in outer space, and what are the most important international conventions that have organized their work, explaining the definition of the satellite and its most important types as well as the launching authority, and the most important principles governing the activities of countries in launching their satellites, Statement of the provisions of international responsibility for damage caused by satellites, to reach the launching State bear international responsibility, which may be an absolute responsibility or responsibility based on error.
Keywords: الأقمار الصناعية؛ السلطة المطلقة؛ الفضاء الخارجي؛ الاستخدام السلمي؛ الضرر؛ المسؤولية الدولية satellites; launching authority; outer space; Peaceful use; damage; International liability